The Fund's Liquidity Position-Review and Outlook. (Policy Papers; Policy Paper ;, 2010)
This paper proposes a new trust fund that would enable the IMF to join international debt relief efforts for Haiti and other low-income countries hit by similar catastrophic disasters. Following the devastation caused by the recent earthquake in Haiti, an international consensus emerged that creditors should consider full debt relief to support Haiti's recovery. Haiti's debt to the IMF stands at SDR 178 million.